Literatures of the world beyond world literature - Ette, Ottmar; Person, Mark W. (Leiden [u.a.] : Brill, 2021)
"Beginning with Erich Auerbach's reflections on the Goethean concept of world literature, Ottmar Ette unfolds the theory and practice of Literatures of the World. Today, only those literary theories which are oriented upon a history of movement are still capable of doing justice to the confusing diversity of highly dynamic, worldwide transformations. This is because they examine transareal pathways in the field of literature. This volume captures literary processes of exchange and transformation between the Mediterranean, Atlantic and Pacific as well as the interplay of different ways of narrating space and time. Thus, this volume speaks from a fractal point of view and unfolds multiple perspectives. Literatures of the World allow the reader to think in different logical frameworks at the same time, therefore shaping our future on the basis of the diversity of humankind"
Preface: Beyond world literature -- "Mimesis" : perspectives from Erich Auerbach's philology of world literature toward a coming philology of the literatures of the world -- From the republic of world literature to a multilogical philology of the literatures of the world -- Before and after the "happy revolution" : Langsdorff, the Berlin debate on the new world, and its impact on scientific expeditions -- Journey/landscapes : (W)Orte (words/places) on the transit of a transareal travel literature -- Carnival and other catastrophes : nature as culture and new Orleans as global archipelago -- Roland Barthes or the multiplication of the East -- The transareality of the Mediterranean : the Mediterranean as migratory space -- Lebensmitte(l) literatur - midst of life, means of life : on the reading of life as a means of living : considerations in connection to Honoré de Balzac's "La Peau de chagrin" -- Unrest as a driving force : on vectoricity and economy of a monumental feeling -- Lyric as concentrated movement : miniaturization and archipelagization in poetry : with the example of a poetic writing without a fixed abode by José F. A. Oliver -- Modernism, convivence, postmodernity : on grafting and "mestizaje" to transarchipelagic coexistence in the americas -- Transarea studies, transAndean studies -- Magische Wände/Magic walls : Biombos, Namban art, and the art of globalization between China, Japan, India, Spanish-America, and Europe in the 17th and 18th centuries.
Literaturverz. S. 441 - 465
Keywords: Weltliteratur; Globalisierung; Lebenswissen